maths

posted by .

rearrange the following equation to find x in terms of y and t

y(y-x)=3t(3t+x)

  • maths -

    multiply out the parenthesis.
    gather the x terms on one side.

    -yx-3tx=-y^2 + 9t^2

    -x(y+3t)= -y^2+9t^2

    now, divide both sides by -(y+3t)

    x= (y^2-9t^2)/(y+3t)

    the numerator is a difference of two squares, so will factor. One of those factors will divide with the denominator.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Calc 2

    Ok, I have two questions first: 1. I'm asked to find a cartesian equation for the polar graph of this polar equation: r^2 = sin(2(theta)) The answer I got was (x^2+y^2)^2/(2xy) = 2 Is this the correct way to express it?
  2. Maths

    I need to rearrange this equation to find x in terms of y and t, in its simplest form. Can anybody help me. y(y-x)=3t(3t+x)
  3. maths

    how would i solve the differential equation dx/dt=-kx^2 i.e. solve for x as a function of t. I've been told to rearrange the equation to yield dx/x^2=-k dt but what can and should I do now?
  4. Math

    Hello.I need to rearrange the following to make b the subject' a = 10/b-z. Im getting confused with how to rearrange when theres division involved.
  5. science

    how do you rearrange 1.1513/sqrt(f)=ln(Re*sqrt(f)/2.51) to get it in terms of f and also rearrange it in terms of Re?
  6. maths

    im trying to rearrange the following equation for x but getting confused because of the brackets and squares. I understand the process of changing the subject but on more simple equations. Please can you help me. Here's the equation …
  7. Chemistry

    How can i rearrange this Clausius-Clapeyron equation so that 1/T2 is on one side?
  8. maths

    How do i rearrange the equation to make d the subject. e = d/ab (d/ab has a square root sign over it)
  9. Geometry

    Given: 7x + 2 = 2 + 5x – 6 Prove: x = –3 Given the equation 7x + 2 = 2 + 5x – 6, use the commutative property to rearrange the terms so that like terms are next to one another. This gives the equation 7x + 2 = 2 – 6 + 5x. Then, …
  10. Maths

    Help me rearrange this equation, v=20-9.8t

More Similar Questions